Computational and experimental results in the open test section of the aeroacoustic windtunnel Braunschweig. (1st January 2013) - Ciobaca, Vlad; Pott-Pollenske, Michael; Melber-Wilkending, Stefan; Wichmann, Georg
This paper discusses results of numerical simulations for low speed open tunnel test section in connection to wind tunnel experiments aiming to assess the computational accuracy. The investigations are performed for the aeroacoustic wind tunnel Braunschweig with and without a mounted experimental model. RANS simulations are performed within a CFD procedure developed to simulate open test sections. In the empty tunnel, measurements of the free shear layers and of the flow fields downstream the nozzle show a good agreement with the predicted flows. The jet core size and its position, as well as the velocity gradients in the mixing layer are simulated mostly accurate. Afterwards, the in-tunnel simulations with a 2D-high lift model are discussed. These reproduce very well the measured global lift force and local flow pressure distributions at moderate angles of attack but show discrepancies at maximum lift. In overall a good agreement of the numerical results compared to the experiments is achieved.